PENGARUH BRAND AMBASSADOR ARTIS AMANDA MANOPO DAN ARYA SALOKA TERHADAP NIAT BELI KONSUMEN MELALUI PERSEPSI RISIKO PADA IKLAN (STUDI PADA SHOPEE INDONESIA) - Fadilah Rizki Solikhah (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2022)
Information technology has progressed very rapidly so that it requires business actors to take advantage of technological advances for the application of their business. Business competition is getting tougher and dynamic with the times, companies often compete and show each other competition through the advertisements they make. This study purpose is to explain and analyze the effect of brand ambassadors on consumer purchase intentions by examining an intervening variable, specifically the perception of risk in advertising. This study employs a technique known as non-probability sampling. This type of research employs descriptive methods, contacting a total of 239 respondents via Google Form. techniques for data analysis utilizing path analysis. The findings of this study indicate that brand ambassadors have a negative and significant influence on risk perception, that risk perception has a negative and significant influence on purchase intention, and that brand ambassadors have a positive and significant influence on purchase intention. Shopee and business actors can use the results of this research to determine the appropriate brand ambassador so that consumers' minds about the risks that occur when doing online shopping are reduced and will later lead to purchase intentions.